REFORMULASI DELIK TINDAK PIDANA PENGHINAAN CITRA TUBUH (BODY SHAMING) DI MEDIA SOSIAL DIKAITKAN DENGAN PRINSIP ASAS LEGALITAS - Nadya Serena Nasution; Mexsasai Indra; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Crime of Body Image Shaming (Body Shaming) is a crime that is rife in Indonesia. Criminalinsulting body image (Body Shaming) gives a bad impact for individuals who experience it such asdepression, and eating disorders. Perpetrators of Criminal Actions for defamation of body image (BodyShaming) can be charged with applicable Laws, although in reality there is no article that specificallyregulates the criminal conduct of body image defamation. There should be a more specific regulationregarding the crime of insulting body image (body shaming) on social media because Indonesia is a countrythat adheres to the principle of legality, if a crime occurs then it will be seen whether there are legalprovisions that govern it and whether the existing rules can be applied to criminal offenses that occur thebody is not ideal and / or not like body shapes in general. Based on this understanding, the authors identifytwo problem formulations, First how to regulate the crime of insulting body image (Body Shaming) in thepresent condition of crime (Body Shamig) on social media in criminal law. Second, how the reformulation ofthe crime of insulting body image (Body Shaming) on social media is related to the principle of legality.This type of research can be classified in normative juridical research, because this research isconducted by examining secondary data and approaches to law, this normative research examines theprinciples of legal principles of law. The data sources used are, primary data, secondary data, tertiary data,data collection techniques in this study are normative juridical, the data used is library research.Based on the results of research and the problem in this study is the regulation of criminal acts thatinsult body image (body shaming) in criminal law in Indonesia refers to Article 315 of the Criminal Codeabout insults and Article 27 Paragraph (3) of the ITE Law. In the ITE Law, there are articles which areconsidered more suitable to ensnare the perpetrators of the crime of insulting body image (Body Shaming).In Article 27 Paragraph (3) of Law Number 11 Year 2008 Changes to Law Number 19 of 2016 ElectronicInformation and Transactions lacks a definite rule regarding body shaming criminal acts which causesmany problems or losses experienced by the victim. The absence of a definite rule regarding the bodyshaming crime has caused many problems or losses experienced by the victim. The need for a legal updaterelated to the existence of regulations and their implementation. The renewal of the ITE Law was carriedout because it was not yet ideally for the crime of insulting body image through social mediaKeywords: Insult, Body Shaming, Criminal Law Renewal